Cationic surfactant-assisted delamination of disorderly layered clinoptilolites for selective adsorption of CO2 and CH4. Issue 3 (June 2022) - Jia, Bingying; Xu, Bang; Bing, Liujie; Sun, Jihong; Bai, Shiyang
Abstract: With the assistance of cetyltrimethyl ammonium bromide (CTAB), the delamination of disorderly layered clinoptilolite (CP) was performed. The introduction of CTAB in hydrothermal system was beneficial to stratification of CP lamellas by enlarging interlayer spacing, and thus accelerating the formation of disordered CP nanosheets. The hydrophobic alkyl chain restricts the crystal growth along a-axis and the few-layer CP lamellas with integrally preserved heulandite structures were obtained by ultrasonic treatment and HNO3 modification at room temperature. Meanwhile, the CTAB-assisted crystallization mechanism was further elucidated, in which, the amorphous spherical nanoparticles were firstly generated and then transformed into the fibrous and lamellar species. Finally, the flower-like CP morphologies with the aggregated nanosheets appeared. Meanwhile, the selective adsorptions and separations of CO2 and CH4 using these delaminated CPs as the absorbents were preliminarily explored, showing a strong potential in the mixed gases separation applications. This approach is a promising strategy for constructing delaminated zeolites with low n(SiO2 /Al2 O3 ), which may open a new avenue for the delaminated CP nanosheet applications in gas adsorption and separation fields. Graphical Abstract: ga1 Highlights: The delaminated clinoptilolite (CP) was obtained by surfactant-assisted exfoliation. The fibrous particles play a vital role in the formation of disorderly layered CPs. 3The delaminated CP shows an advanced separation performance of CO2 and CH4 .